Detection of subclinical autonomic neuropathy in constipated patients using a sweat test. Issue 11 (November 1992) - Altomare, D; Pilot, M A; Scott, M; Williams, N; Rubino, M; Ilincic, L; Waldron, D
Abstract : Chronic idiopathic constipation may be the result of an autonomic neuropathy. This hypothesis was tested in 23 constipated patients and 17 age matched controls, using the acetylcholine sweat spot test devised to test autonomic integrity in diabetes. Acetylcholine (0.01%) was injected in the dorsum of the foot painted with a mixture of starch and iodine. Active sweat glands appeared on the surface of the skin as small black dots which were photographed and counted, using a grid with 60 subareas. Two measurements were made: the number of dots per unit subarea (sweat spot test score) and the % number of abnormal subareas (with less than six spots). These two parameters were correlated. The median sweat spot test score was 9.53 in patients and 13.92 in controls (p = 0.0001), the receiver operating characteristic curve showing that a score of 12 delimited normal and abnormal subjects. Increasing age was correlated with a low score in patients, probably because of prolonged symptoms. Seventy per cent of patients and one control had a borderline or abnormal number of subareas. These results suggest that idiopathic constipation is associated with a degree of autonomic denervation. The sweat spot test is an easy, inexpensive method to test this hypothesis and deserves a place in the clinical assessment of slow transit constipated patients.